Stateless Filipino children in modern day Sabah: issues of concern and responses of the state government - Mohd Afsur Khan, Jassica Jane; Fathil, Fauziah (IIUM Press, International Islamic University Malaysia, 2020)
Stateless children have been an ongoing issue specifically in Sabah state for years since independence in 1963. The civil war back in the late 1960s in Southern Philippines saw a tremendous number of refugees from the country seeking refuge in Sabah. They were among the earliest refugees from Mindanao that came to the state whose presence over the years has resulted in the rising number of stateless children of Filipino origin. Although being born and raised in Sabah, legally the children are not citizens of Sabah due to the absence of proper documentation of birth records or certificates. This paper is based on a qualitative study using content analysis. The analysis involves mainly secondary sources with the aim to shed light on the root cause of the issue and identify actions taken by the Sabah government towards finding solutions to the problem. In doing so, the study is assessed against the standpoint and response of the Sabah government, the background of Filipino migrants in Sabah and their stateless children, and the socio-economic and political contexts of the state as a whole. The findings indicate that the root cause of the issue is very complicated and despite some actions taken by the Sabah government, the matter continues to persist affecting not only the refugees and their stateless children but the local people and state of Sabah. Finally, the paper ends with some recommendations i.e. several proposed actions to be taken by relevant parties so that the issue which has been ongoing for decades in Sabah and affected the lives of so many children could be finally solved.